La disminución de la pobreza en Venezuela entre 2001 y 2007 : alcance y sostenibilidad - Claudia Giménez Mercado; Silverio González Téllez; Emiro A. Molina Cuevasas (Cahiers des Amériques Latines)
This article addresses the study of the diminishing poverty in Venezuela between 2001 and 2007. With the application of the properties of additive decomposition, from the family of measures proposed by Foster, Greer, and Thorbecke, to the data received from the surveys on households conducted by Muestreo (National Institute of Statistics), we can obtain results that allow for the comparison of households touched by poverty in Venezuela between 2001 and 2007. This data illuminates the factors that prove a decrease in poverty. We then do a comparison based on the measures of structural poverty, like “The Index of Unsatisfied Basic Needs” and the “Human Poverty Index”. Furthermore, the household incomes are broken down to enable us to examine their components to identify the portion of the revenue which has contributed the most to the decrease of poverty during that time period. The structure itself of the households was also examined through variables traditionally linked to poverty, in order to evaluate the socio-economic change which occurred. In fact, the observed decrease comes more from an increase in non-professional revenues of the household – notably from governmental money transfers, or money from parents – than an augmentation of revenues gained from productive work by members of the household. This phenomenon is closely linked to an increase in public spending generated by the petroleum-based prosperity of the State. This increase did not translate into structural changes sufficient to better the conditions of life of the population, nor will these changes prevent a new increase in poverty when this petroleum-based prosperity has passed. Therefore, it is crucial that adjustments be made. In fact, what is happening there is a cycle that the economy and petroleum interests of Venezuela have experienced many times in the last half-century.